1976
DOI: 10.1111/j.1365-246x.1976.tb01279.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of rotational remanent magnetization

Abstract: Rotational Remanent Magnetization (RRM) occurs when ferromagnetic rock specimens are AF demagnetized while rotating slowly. An extensive study of the properties of this remanence has been made in an attempt to determine its formation mechanism. Experiments on good conductors and soft magnetic materials rotating in steady magnetic fields show no corresponding magnetic effects. It is also shown that RRM is not an inertial effect and cannot be produced during thermal magnetization. A comparison of the AF demagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 5 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…The magnitude of GRM might be expected to depend on the flip time of the particle moment, termed this the rotational remanent magnetization (RRM). Since then, a substantial amount of work on RRM has been the degree of anisotropy, and the angle h between A and F, and will be minimum when h is 0°or 90°, and maximum when published (Brock & Iles 1974;Stephenson 1976;Hillhouse 1977;Edwards 1980a,b). A gyromagnetic origin for RRM, h is 45° (Stephenson 1980b;Roperch & Taylor 1986).…”
mentioning
confidence: 99%
“…The magnitude of GRM might be expected to depend on the flip time of the particle moment, termed this the rotational remanent magnetization (RRM). Since then, a substantial amount of work on RRM has been the degree of anisotropy, and the angle h between A and F, and will be minimum when h is 0°or 90°, and maximum when published (Brock & Iles 1974;Stephenson 1976;Hillhouse 1977;Edwards 1980a,b). A gyromagnetic origin for RRM, h is 45° (Stephenson 1980b;Roperch & Taylor 1986).…”
mentioning
confidence: 99%
“…Later experiments confirmed these initial findings and examined the importance of the relative orientation and frequencies of the specimen rotation and alternating field (Brock & Iles 1974;Edwards 1980aEdwards , 1984Stephenson 1985). Further work has compared the characteristics of RRM with other modes of remanence (Edwards 1980b(Edwards , 1984Stephenson 1976). It is believed that RRM may explain the erratic changes in remanence that are sometimes produced by alternating field demagnetizers which tumble the specimen.…”
Section: Introductionmentioning
confidence: 93%
“…There have been several other works broadly similar to that described in this article. Stephenson (1976) progressively demagnetized an ARM, and an RRM, each acquired in an A F of 60 mT, in A F s of strengths up to 40 mT and concluded that there is a fundamental difference between ARM and RRM demagnetization curves. In separate studies Stephenson (1985;1983, respectively) has given theoretical accounts of the acquisition of PRARM, and the acquisition and subsequent static demagnetization of ARM.…”
Section: Introductionmentioning
confidence: 99%